Association of Bisphosphonate Use and Risk of Revision After THA: Outcomes From a US Total Joint Replacement Registry - Khatod, Monti (Clin Orthop Relat Res, 2015)
BACKGROUND: Total hip arthroplasty (THA) is often performed in patients who are older and may take bisphosphonates to treat a variety of conditions, most commonly osteoporosis. However, the clinical effects of bisphosphonate use on patients who have undergone THA are not well described. QUESTIONS/PURPOSES: (1) Is bisphosphonate use in patients with osteoarthritis undergoing primary THA associated with a change in the risk of all-cause revision, aseptic revision, or periprosthetic fracture compared with patients not treated with bisphosphonates? (2) Does the risk of bisphosphonate use and revision and periprosthetic fracture vary by patient bone mineral density and age? METHODS: A retrospective cohort study of 12,878 THA recipients for the diagnosis of osteoarthritis was conducted; 17.8% of patients were bisphosphonate users. Data sources for this study included a joint replacement registry (93% voluntary participation) and electronic health records and an osteoporosis screening database with complete capture of cases as part of the Kaiser Permanente integrated healthcare system. The endpoints for this study were revision surgery for any cause, aseptic revision, and periprosthetic fracture. The exposure of interest was bisphosphonate use; patients were considered users if prescriptions were continuously refilled for a period equal to or longer than 6 months. Bone quality (based on dual-energy x-ray absorptiometery ordered based on the National Osteoporosis Foundation’s clinical guidelines taken within 5 years of the THA) and patient age (< 65 versus ≥ 65 years) were evaluated as effect modifiers. Patient, surgeon, and hospital factors were evaluated as confounders. Cox proportional hazards models were used. Hazard ratios (HRs) and 95% confidence intervals (CIs) were determined. RESULTS: Age- and sex-adjusted risks of all-cause (HR, 0.50; 95% CI, 0.33–0.74; p < 0.001) and aseptic revision (HR, 0.53; 95% CI, 0.34–0.81; p = 0.004) was lower in bisphosphonate users than in nonusers. The adjusted risk of periprosthetic fractures in patients on bisphosphonates was higher than in patients not on bisphosphonates (HR, 1.92; 95% CI, 1.13–3.27; p = 0.016). Lower risks of all-cause revision and aseptic revision were observed in patients with osteopenia (HR, 0.49; 95% CI, 0.29–0.84; and HR, 0.53; 95% CI, 0.29–0.99, respectively) and osteoporosis (HR, 0.22; 95% CI, 0.08–0.62; and HR, 0.33; 95% CI, 0.11–0.99, respectively). CONCLUSIONS: Patients considered bisphosphonate users who underwent THA had a lower risk for revision surgery. Bisphosphonate use was associated with a higher risk of periprosthetic fractures in younger patients with normal bone quantity. Evaluation of bone quality and bisphosphonate use for the diagnosis of osteoporosis is encouraged in patients with osteoarthritis who are candidates for primary THA. Further research is required to determine the optimal duration of therapy because long-term bisphosphonate use has been associated with atypical femur fractures. LEVEL OF EVIDENCE: Level III, therapeutic study.